Business Owners Perceptions and The Quality Financial Reports: The Moderating Role Accounting Training - Ristyvia, Reva; Kristiawati, Endang; Setiawan, Aris (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This paper aims to examine business owners' perceptions of the quality MSME financial reports with accounting training as a moderating variable, and analyze role of accounting training in strengthening or weakening this relationship. The sampling technique in this study used purposive sampling, which is a sampling technique based on certain criteria tailored to the research needs. The number of samples obtained was 107 respondents. This number is considered adequate because the data analysis was conducted using the SEM-PLS approach using SmartPLS 3. The results of the study indicate that the relationship between owner perceptions of the quality of financial reports has a positive effect. Accounting training as a moderating variable has an influence on owner perceptions of the quality of financial reports, but the influence shows a negative value, meaning it is weakening. This can be interpreted as the higher the level of owner perceptions of the importance of financial reports, the lower the level of accounting training because owners rely more on their knowledge and skills. Awareness and views of MSME entrepreneurs regarding the importance of accounting understanding can improve the quality of financial reports and business sustainability.